(untitled) (Bangladesh Journal of Agricultural Research, 2020)
The experiment was conducted at Agronomy field of Bangladesh Agricultural Research Institute, Gazipur during 2016-2017 and 2017-2018 to determine the nutrient requirement for yield maximization of Bt brinjal (var. BARI Bt Begun-2). The treatments were T1= STB (soil test base) recommendation (120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B+ 3 t/ha poultry manure), T2 = T1 + 25% of N-P-K-S-Zn-B (150-45-112-18-2.5-1.25 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure), T3= T1 + 50% of N-P-K-S-Zn-B (180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure), T4= T1 + 25% of N-P-K-S-Zn-B + 3 t/ha poultry manure (150-45-112-18-2.5-1.25 kg/ha N-P-K-S-Zn-B+6 t/ha poultry manure), T5= T1 + 3 t/ha poultry manure (120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B + 6 t/ha poultry manure). Nutrient uptake, yield components and yield of Bt brinjal varied significantly due to variation of nutrients in the tested years. The highest plant height (98-116 cm), canopy coverage (1.21-1.26 m2/plant), number of fruits/plant (57.69-59.23) and individual fruit weight (83-86 g) were obtained from 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure (T3) treatment where days to flowering showed the lowest values (109-110 days). The highest pooled yield (58.46 t/ha) of Bt brinjal was observed from the treatment 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure(T3) and the lowest (23.39 t/ha) from 120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B+ 3 t/ha poultry manure) (T1). The highest nutrient uptake (214-43-208-60-0.38-0.213-49 kg/ha N-P-K-S-B-Ca) was also observed from the same treatment (T3). Fruit yield showed a strong (r=0.97) linear relationship with applied nutrients. Effect of nutrient application on fruit yield of Bt brinjal was estimated about 86%. The highest gross return (Tk. 587900/ha), gross margin (Tk. 417660/ha) and benefit cost ratio (3.45) were obtained by applying 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B+3 t/ha poultry manure. Results revealed that application of 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B along with 3 t/ha poultry manure would be economically optimum for achieving higher yield of Bt brinjal grown under Grey Terrace soil (Aeric Albaquept) of Gazipur. Bangladesh J. Agril. Res. 44(4): 591-598, December 2019